ChemInform Abstract: Microwave‐Assisted [3 + 2] Cycloaddition and Suzuki—Miyaura Cross‐Coupling for a Concise Access to Polyaromatic Scaffolds. Issue 19 (13th May 2014) - Hedou, Damien; Deau, Emmanuel; Dubouilh‐Benard, Carole; Sanselme, Morgane; Martinet, Anthony; Chosson, Elizabeth; Levacher, Vincent; Besson, Thierry
Abstract Under these conditions a number of novel pyridopyrimidinone and quinazolinone derivatives can be prepared rapidly.